CRIMINOLOGICAL CHARACTERISTICS AND ANALYSIS OF CRIMES IN BANKING SECTOR - Herasymov, O. V. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2017)
the article considers the problem of determining the range of elements that make up the criminological characteristics of crimes in the banking sector. The author’s definition of the term "criminological characteristics of crimes in the banking sphere" is presented and argued. The correlation between concepts "criminological characteristic" and "criminological analysis" is determined. Consider the main methods of criminological analysis of crime in the banking sector. Explored their advantages and disadvantages.